Handbook of research on global environmental changes and human health - Kahime, Kholoud, 1986-; Hidan, Moulay Abdelmonaim El; Hiba, Omar El; Sereno, Denis; Bounoua, Lahouari (Advances in environmental engineering and green technologies (AEEGT) book series., 2019)
"This book examines climate change with particular reference to all factors of sensitivity and exposition to climate change that threaten population health and well-being. It also explores some health adaptation strategies and policies that can improve health systems and reduce many climate change effects"--